A Model for Managing the Performance of CMMS Deployment in High-Rise Office Buildings: A View from Lagos, Nigeria. (16th November 2021) - Musa, Shamsudeen; Nisham Musa, Zairul; Chua, Shirley Jin Lin
Abstract : The development of high-rise buildings is a current trend in developed cities to answer the challenges of population growth, adding aesthetic value, and optimal use of land. Lagos particularly is one of the fastest growing cities in the world with Gross Domestic Product (GDP) and Internally Generated Revenue (IGR) in Nigeria, which suggests the need for multiple complex buildings, and the need for their maintenance cannot be overemphasised. This maintenance aspect requires tremendous work due to the complexity attached and several strategies springing up. Different studies reveal that both performance measurements and factors are essential aspects in evaluating maintenance management. Thus, this study seeks to explore performance elements that could improve maintenance. Personnel attitude, maintenance policy, maintenance review, and maintenance implementation were measured relative to computerised maintenance management system (CMMS) performance. With a random sampling technique, a sample of 134 Facility Management (FM) practitioners involved in high-rise office buildings was used to assess the effects of CMMS deployment. Results were analysed by Partial Least Squares Structural Equation Modelling (PLS-SEM). Findings from this study highlighted an indirect effect size and a large predictive relevance of personnel attitude as a critical factor for a smooth maintenance execution procedure of 12.59% and a standard operating procedure (SOP) of 15.64% on maintenance implementation to contribute 28.36% to performance. This paper uncovers the place of personnel attitude in determining effective maintenance.